Sulfated Polysaccharide From Undaria Pinnatifida Induces Apoptosis and Inhibits Proliferation, Migration, and Invasion in Ovarian Cancer via Suppressing the Hedgehog Signaling Pathway - Yang, Yi; Zhang, Qin; Xu, Yongping; Chen, Gang; Qiu, Yukuan (Frontiers in Materials, 2021)
Objective To investigate the effects of sulfured polysaccharide from Undaria pinnatifida (SPUP) on the biological behaviors of ovarian cancer (OC) cells and its potential mechanism. Methods Sulfated polysaccharide from Undaria pinnatifida (SPUP) was extracted and characterized through a combination of chemical analysis, IR spectra, UV-Vis, gas chromatography and high-performance gel permeation chromatography. OC and human ovarian surface epithelial cells were used as working model in vitro for evaluation of SPUP’s therapeutic effects. A combination of CCK-8, Transwell and flow cytometry assay was used to measure the proliferation, migration, invasion, and apoptosis of OC cells, respectively. In addition, the protein expression levels of cells were also measured by Western blot. Results SPUP suppressed OC development from three different perspectives: 1) SPUP treatment significantly inhibited the proliferation of OC in dosage-dependent manner (p<0.05); 2) SPUP inhibit the migration and invasion of OC cells confirmed by scratch and Transwell experiments (p<0.05); 3) SPUP induced apoptosis in OC cell thus further inhibit the growth of OC cells evaluated using Flow cytometry (p<0.05). The underlying mechanism of the suppressing effects of SPUP might be related to the inhibition of hedgehog signaling pathway in OC cells after SPUP treatment. With additional suppression of hedgehog signaling pathway, the anticancer effects of SPUP were enhanced (p<0.05). Conclusion Taken together, SPUP could inhibit the proliferation, migration, invasion and induce apoptosis of OC cells by inhibiting the activation of hedgehog signaling pathway, which proposing SPUP as a novel drug to treat OC clinically.